Pelatihan Penyusunan Rencana Perjalanan Berbahasa Mandarin di SMK Taman Siswa Purwokerto - Destyanisa Tazkiyah; Zuyinatul Isro; Berliana Cantika Putri (Jurnal Pengabdian Masyarakat (abdira), 2022)
As a form of service in the field of tourism, this  community service aims to prepare prospective graduates of the Taman Siswa Vocational School majoring in tourism to have basic skills in preparing travel plans for Chinese tourists. The number of Chinese tourists ranked second after Malaysia based on BPS data at the end of 2019 before the Covid pandemic, this must be balanced with an increase in good service or hospitality. One of them is by empowering tourism human resources who are able to speak Mandarin. This service activity is one of the efforts that can prepare students to be ready to enter the world of tourism, both during the new normal pandemic or when things have returned to normal. The method used in the implementation of this activity is the mentoring method. As a result of this training activity, the students succeeded in learning basic Mandarin in the tourism sector, and were able to develop a typical Banyumas travel plan in Mandarin based on the new normal of the Covid-19 pandemic.